Designing a Hypothetical Learning Trajectory with Student Worksheets: Fostering Collaboration and Innovation in Probability Learning - Indraswari, Annisa Yora; Shodikin, Ali (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2025)
This study aims to develop a Hypothetical Learning Trajectory (HLT) based on student worksheets for teaching probability as an innovative approach to enhance students’ conceptual understanding. The development is driven by the need for instructional design that connects abstract mathematical concepts to real-life contexts. The research adopts a design-based research (DBR) approach through an in-depth case study of three eleventh-grade students. Data were collected through LKPD tasks, observations, semi-structured interviews, and diagnostic tests. Findings show that the HLT-based student worksheet effectively supported students’ progressive understanding of probability, fostering intuitive exploration and formal application. Students demonstrated active engagement, cognitive growth, and positive attitudes toward learning. The study concludes that implementing HLT through LKPD is a valid and promising strategy to improve the quality of mathematics instruction, particularly in the topic of probability.